Peaditric's first aid (seizure: sawan) - Muhd Helmi, Muhd Alwi; Anuar, Muhamad Azamin; Mohamad Khairi, Siti Nur Lina; Ahmed, Ebrahim Adel Ali (2021)
Training module for nursery and kindergarten teachers on first aid management of seizure line training.